Lithium-ion Battery Degradation with Application to Wave Energy Converters - Jayasinghe, A.E.; Fernando, N.; Wolgamot, H.; Apsley, J.; Stansby, P.; Kumarawadu, L.; Wang; Gaudin, C. (Blue Economy Cooperative Research Centre, 2024)
Wave Energy Converters (WECs) enable renewable power extraction from ocean waves. The intermittent and dynamic behaviour of wave energy requires capture and storage of energy extracted by the WEC. This work investigates the use of Lithium-ion batteries (LIBs) in this application. LIBs offer high energy density, fast response, low self- discharge rate, and high performance. However, the dynamic nature of the power generation pattern in application to a WEC may result in the degradation of LIBs due to dynamic nature of the charge-discharge cycles. This work investigates the application of a LIB electrochemical model coupled with a dynamic simulation of a Moored Multi-mode Multibody Power Take-off System to demonstrate the capability to predict LIB degradation using simulations. The State of Health (SOH) of the LIB is used as an indicator for battery degradation based on capacity reduction. The work will also present the simulation results of potential increase in lifetime by having supercapacitor energy storage to mitigate the rapid energy transfer from the LIB.
Keywords: Lithium-ion battery; Battery Modelling; Wave energy converters; Electrochemical Impedance Spectroscopy